PENGARUH PENERAPAN HARGA POKOK PENJUALAN TERHADAP HARGA JUAL DONAT MOCHI “DONAÉ” - Della Puspita Sari; Herni Kurniawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
The culinary industries is a promising sector increasingly pursued by younger generations. In Indonesia the industries has grown quite rapidly and was overwhelmed with new start-up businesses in the industry. In the culinary industry, innovation can be achieved on the products by implying on product innovation, packaging, marketing strategies, and operational management. Through the Merdeka Belajar Kampus Merdeka (MBKM) program, students are given the opportunity to contribute fully to community service activities in order to enlarge culinary business ideas through practical experience. This activity emphasizes guidance in determining the right selling price using the Cost of Goods Sold (COGS) approach, product innovation, and simple financial management. Setting the right selling price is one of the main challenges in entrepreneurship. The application of Cost of Goods Sold (COGS) as the basis for determining selling prices, taking into account raw material costs, production processes, and the desired profit margin, not only affects product competitiveness but also plays a vital role in maintaining business sustainability and profitability. This community service project focuses on assisting the development of a donut business under the brand “Donae” as a build of student entrepreneurship in the culinary sector as well as emphasizing the importance of integrating financial and entrepreneurial aspects in establishing effective selling prices in the mochi donut business. Through mentoring and direct application, students will expand their knowledge of the balance between affordable prices for consumers and sustainable profits for businesses. Kewirausahaan di bidang kuliner merupakan sektor yang menjanjikan dan semakin diminati oleh generasi muda. Di Indonesia, industri ini telah berkembang dengan cukup pesat dan dibanjiri oleh bisnis startup baru di bidang kuliner. Di industri kuliner, inovasi dapat dicapai melalui inovasi produk, kemasan, strategi pemasaran, dan manajemen operasional. Melalui program Merdeka Belajar Kampus Merdeka (MBKM), mahasiswa diberikan kesempatan untuk berkontribusi penuh dalam kegiatan pengabdian kepada masyarakat guna mengembangkan ide bisnis kuliner melalui pengalaman praktis. Kegiatan ini menekankan pendampingan dalam penentuan harga jual yang tepat menggunakan pendekatan Harga Pokok Penjualan (HPP), inovasi produk, serta pengelolaan keuangan sederhana. Menentukan harga jual yang tepat adalah salah satu tantangan utama dalam kewirausahaan. Penerapan Harga Pokok Penjualan (COGS) sebagai dasar penetapan harga jual dengan mempertimbangkan biaya bahan baku, proses produksi serta tingkat persentase laba yang diinginkan, tidak hanya mempengaruhi daya saing produk tetapi juga berperan penting dalam menjaga keberlanjutan dan keuntungan usaha. Pengabdian ini berfokus pada pendampingan pengembangan usaha donat dengan merek “Donae” sebagai bentuk implementasi kewirausahaan mahasiswa di sektor kuliner serta menekankan pentingnya mengintegrasikan aspek keuangan dan kewirausahaan dalam menetapkan harga jual yang efektif dalam usaha donat mochi. Melalui pendampingan dan penerapan langsung, mahasiswa akan memperluas pengetahuan tentang keseimbangan harga antara harga terjangkau bagi konsumen dengan keuntungan berkelanjutan bagi pelaku usaha.